2006
DOI: 10.1063/1.2357005
|View full text |Cite
|
Sign up to set email alerts
|

Al 0.15 Ga 0.85 N ∕ Ga N high electron mobility transistor structures grown on p-type Si substrates

Abstract: We report on experimental studies of Al0.15Ga0.85N∕GaN high electron mobility transistor (HEMT) structures grown on p-type Si (111) substrates. By introducing an ultrathin SiN layer during the crystal growth, the Hall mobility of the HEMT structure can be greatly enhanced (greater than three times). This SiN treatment technique also allows the observation of Shubnikov–de Haas oscillations which is not possible in the untreated HEMT structure. Our experimental results pave the way for the integration of AlxGa1−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…1,6 Three-dimensional simulation has been carried out to depict the current density distribution in solder bumps and a hot spot was proposed to occur at the region of current crowding. 7,8 The current crowding induced by electromigration still plays a crucial role in the failure of the bumps. Recently, due to environmental concerns, studies have been conducted on the electromigration of lead-free solder bumps.…”
Section: …Describe This Work To a Layperson?mentioning
confidence: 99%
“…1,6 Three-dimensional simulation has been carried out to depict the current density distribution in solder bumps and a hot spot was proposed to occur at the region of current crowding. 7,8 The current crowding induced by electromigration still plays a crucial role in the failure of the bumps. Recently, due to environmental concerns, studies have been conducted on the electromigration of lead-free solder bumps.…”
Section: …Describe This Work To a Layperson?mentioning
confidence: 99%
“…11,12) Recently, it has been shown that by introducing an ultrathin SiN x film during crystal growth, the Hall mobility of a GaN/Al 0:15 -Ga 0:85 N heterostructure on Si could be markedly increased (>3 times). [13][14][15] These GaN/Al 0:15 Ga 0:85 N heterostructures grown on Si are compatible with complementary metaloxide-semiconductor technology and have promising device applications, making it useful in understanding the fundamental physics of these heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Recently GaN/AlGaN heterostructures have attracted much interest because of their application in electrical, light-emitting devices, and high-electron-mobility transistors (HEMTs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The electronic properties of a GaNbased device are governed by the two-dimensional electron system (2DES) formed in the GaN/AlGaN quantum well.…”
Section: Introductionmentioning
confidence: 99%